GENERATION OF TRIANGULAR MESHES FOR COMPLEX DOMAINS ON THE PLANE - Jurczyk, Tomasz; Glut, Barbara (Computer Science, 2020)
Many physical phenomena can bc modelcd by partial diffcrcntial cąuations. The dcvclopmcnt of numcrical methods bascd on the spatial subdivision of a domain into fmitc clcmcnts immcdiatcly cxtcnded interests to the tasks of generating a mesh. With the availability of vcrsatilc field solv- crs and powerful computcrs, the simulations of cver inereasing gcometrical and physical com- plcxity arc attempted. At somc point the main bottleneck becomcs the mesh generation itsclf.The papcr prcsents a dctailcd description of the triangular mcsh gcneration schcmc on the piane bascd upon the Dclaunay triangulation. A mcsh generator should be fully automatic and simplify input data as much as possible. It should offer rapid gradation from smali to large sizes of elcmcnts. The generated mcsh must be always valid and of good quality. Ali thesc rcquiremcnts were taken into account during the selection and elaboration of utilized algorithms.Successive chapters describe procedures connected with the specification of a modeled domain, gcneration and triangulation of boundary vertices, introducing inner nodes, improving the quality of the crcated mcsh, and renumbering of vertices.